Burr reduction in micro-milling processes - Koh, Dong Yang. (2009)
Abstract Micro-sized products have been the growing trend in today’s world, ranging from electronic products to biomedical usage. Different techniques have been used to produce micro-products, and research is continuing to improve the manufacturing techniques. One key area of research is the manufacturing of master template for hot embossing of disposable micro-fluidic devices to be used in the medical field. The current technology is time consuming and costly in producing disposable medical products. In this project, we study the burrs formed while machining of micro-channels on aluminum alloy substrates, using different set of parameters. Such micro-machined substrates can be used as tools for embossing micro-fluidic channels. Using a tapered end mill and normal end mill, different milling top-cutting parameters are tested to study burr formation. The parameters are depth per cut, spindle speed (RPM), feed rate and the direction of milling. Comparison is done, using SEM pictures, between tapered end mill and normal end mill to determine whether there is any difference. The profile of the channel and surface roughness of the side walls are also studied to compare the two tools’ performance. Some phenomenon observed from the results of the machining are also discussed.